Synthesis and Characterization of Zeolite Y From Bagasse Ash with Hydrothermal Temperatures Variations Using The Sol-Gel Method - Ali, Soifi; Amalia, Suci; Fasya, Ahmad Ghanaim (ALCHEMY, 2015)
Zeolite Synthesis Y is done using sol-gel method on the molar composition of 10Na2O: 15 SiO2: x Al2O3: 300 H2O with Si/Al on ratio of 2,43 and hydrothermal temperatures variations of 60, 80 and 100 °C. Characterization includes XRD to discover crystallinity and the purity of zeolite, FTIR for the analysis of functional groups and of the surface width with the adsorption of methylene blue. XRD result shows that the formed zeolites Y is still mixed with zeolite P, the best result in synthesis with hydrothermal temperatures of 80 °C. FTIR analysis showsthat all zeolite synthesis contain a common functionO-Si-O/O-Al-O and double ring. The surface area of zeolite Y at 60, 80 and 100 °C is 22,5522; 23,0603 and22,9898m2/gram. Keywords: Bagasse, sol-gel, temperature hydrothermal, zeolite Y